Social design cook-book : recipes for social cooperation. - Bujdoso, Attila (Budapest : Kitchen Budapest, 2019)
The 'Social Design Cookbook' uncovers what it takes to organise successful and sustainable social initiatives. It features comprehensive case studies of a broad international selection of social cooperative formats that have been effective in their local communities and were also successfully replicated in other locations and contexts. By examining an array of such practices, the authors have developed the “Social Design Canvas”, which can be used to analyse and design new forms of social collaboration and cooperation.
boek